Improving the Fharmacology Teaching-Learning Process in the Formation of Medicine Doctors: Conceptions, Challenges and Perspectives - Pedro Miguel Milián Vázquez; María Magdalena López Rodríguez del Rey (Medisur)
Pharmacology is a discipline that provides medicine doctors with a scientific support for therapies while applying an integral treatment to patients. This article analyzes conceptions, challenges and perspectives of the teaching-learning process of this discipline in Cuba. The author supports the statement of an integral conception of the teaching-learning process, highlighting the sequence of pharmacological teaching tasks throughout the students’ curricula, looking for the interdisciplinary relationship in the different contents in the curriculum of the medicine doctor. Taking this conception as a starting point, the author also states challenges and perspectives, so that the pharmacological contents become appropriate and relevant as part of medicine studies. This presupposes the design of a system for scientific and pedagogical preparation of all teachers in Pharmacology contents they need to complete the appropriate formation of medicine doctors.